The Microbiome of Potentially Malignant Oral Leukoplakia Exhibits Enrichment for Fusobacterium, Leptotrichia, Campylobacter, and Rothia Species - Amer, Abdrazak; Galvin, Sheila; Healy, Claire M.; Moran, Gary P. (Frontiers in Microbiology, 2017)
Oral leukoplakia presents as a white patch on the oral mucosa and is recognised as having significant malignant potential. Although colonisation of these patches with Candida albicans is common, little is known about the bacterial microbiota of these patches. In the current study we analysed the microbiome of oral leukoplakia in 36 patients compared to healthy mucosal tissue from the same patients and healthy control subjects to determine if specific microbial enrichments could be identified early in the malignant process that could play a role in progression. This was carried out by sequence analysis of the V1-V2 region of the bacterial 16S rRNA gene using the Illumina MiSeq. Oral leukoplakia exhibited increased abundance Fusobacteria and reduced levels of Firmicutes (Metastats P <0.01). Candida colonisation was also more prevalent in leukoplakia patients relative to healthy controls (P 0.025). Bacterial colonisation patterns on oral leukoplakia were highly variable and five distinct bacterial clusters were discerned. These clusters exhibited co-occurrence of Fusobacterium, Leptotrichia and Campylobacter species (Pearson P <0.01), which is strikingly similar to the microbial co-occurrence patterns observed on colorectal cancers (Warren et al., 2013). Increased abundance of the acetaldehydogenic microorganism Rothia mucilaginosa was also apparent on oral leukoplakias from lingual sites (P 0.0012). Severe dysplasia was associated with elevated levels of Leptotrichia spp. and Campylobacter concisus (P <0.05). Oral leukoplakia exhibits an altered microbiota that has similarities to the microbiome of colorectal cancer.